ANALISIS SISTEM INFORMASI AKUNTANSI PADA SIKLUS MANAJEMEN SUMBER DAYA MANUSIA DI ABIPRAYA-TGP-SUPRAHARMONIA KSO - Khoirunnisa, Aatika (Jurnal Ilmiah Akuntansi Rahmaniyah, 2024)
The purpose of this study is to ascertain and assess if the Abipraya-TGP-Supraharmonia KSO Penajam Paser Utara Regency's human resource accounting information system has adhered to the fundamentals of efficient internal control. This paper also looks at the payroll system in Abipraya-TGP-Supraharmonia KSO Penajam Paser Utara Regency, pointing up any implementation flaws and providing fixes. Descriptive research analysis is used in this study, and literature reviews, interviews, and observation are used as data gathering techniques. The study's findings show that because contract workers' workloads differ from those of applicable wages, there is an improper payroll system in place. Every month, the HR department of the company ought to issue a Director's Decree outlining the contract employees' payroll status. Recruitment, acceptance, placement, education and training, career development, remuneration, termination of employment, retirement, and salary are among the tasks carried out by the HR information system.